Where Qualitative Researchers and Technologies Meet: Lessons From Interactive Digital Art. (December 2017) - Jackson, Kristi
Drawing from research and theory on interactive digital art (specifically) and the social shaping of technology (more generally), this investigation challenges common conceptualizations of the use of Qualitative Data Analysis Software (QDA Software). Through new frameworks for understanding qualitative research practice, the author pushes QDA Software developers, users, and critics to better understand the entangled relationships between qualitative researchers and digital tools for qualitative research. This is achieved by examining four displays of interactive digital art to disrupt the fairly simplistic binaries such as software/methods, researcher/technology, and automated/manual. After a focus on the experience of visitors to these displays, the article concludes with the analogy of the ideal qualitative researcher as a "good visitor" to emphasize the local, dynamic, engaged, and experiential aspects of respectfully and productively collecting and analyzing relevant qualitative data, regardless of whether a researcher uses digital tools to do so or not.